Novel Insights of Lithium Chloride Therapeutic Approach for Managing Type 2 Diabetic Kidney Disease: Crosslinking Tau Hyperphosphorylation and TGF Beta Signaling - Layal Abou Assi; Fatima A. Saleh; Mahmoud I. Khalil; Assaad A. Eid (Diabetology)
Background: Diabetic kidney disease (DKD) represents a chronic microvascular complication with diabetes, affecting around one-third of diabetic individuals. Despite current therapies, progression to end-stage kidney disease remains a challenge. Abnormal hyperphosphorylation of the Tau protein is implicated in various age-related diseases. This study aimed to explore the link between renal Tau protein hyperphosphorylation and kidney damage in type 2 diabetes mellitus (T2DM). Methods: Sprague Dawley rats were administered lithium chloride (LiCl), an inhibitor of a glycogen synthase kinase-3 (GSK3) inhibitor known to reduce Tau hyperphosphorylation. LiCl was administered either daily or every other day at a dosage of 1 mmol/kg. The effects of LiCl on kidney function were assessed through proteinuria, the kidney-to-bodyweight ratio, inflammation, fibrosis, and TGF-β1 expression levels. Results: Diabetic rats exhibited increased proteinuria, renal hypertrophy, inflammation, fibrosis, and elevated TGF-β1 expression. Lithium chloride treatment reduced kidney hypertrophy, inflammation, and fibrosis, indicating that Tau hyperphosphorylation contributes to the pathogenesis of DKD. LiCl also regulated TGF-β1 expression, which was associated with improved renal outcomes. Conclusions: The inhibition of Tau hyperphosphorylation by lithium chloride offers a potential therapeutic strategy for mitigating kidney damage in diabetic kidney disease. This study proposes LiCl as a novel treatment approach to attenuate DKD progression.